Reconstruction of facial defects using a pre-expanded scalp flap: A description of the method used and outcomes of 43 patients - Ding, Jianke; Chu, Feifei; Tang, Yinke; Liu, Shiqiang; Zeng, Xianhui; Yang, Qing; Ma, Xianjie (Frontiers in Surgery, 2022)
Background: A technique for reconstructing facial units with matching colour, similar texture and sufficient contour is ideal for patients with various facial defects. The current report aimed to present the experience of the authors in facial reconstruction using pre-expanded scalp flaps combined with laser hair removal. Methods: From January 2014 to August 2021, 43 patients with different facial defects, such as post-burn scar and congenital nevus, were treated using this surgical technique that involved tissue expansion, scalp flap transfer and laser hair removal. Facial defects were artificially classified into three regions (forehead, n = 19; cheek, n = 15; and lips and chin, n = 9). Pedicle delaying and division were performed in patients who underwent reconstruction with pedicled flaps. Results: Of the included patients, one presented with haematoma, one with infection and three had distal necrosis after expanded scalp flap transfer. The donor site was primarily closed in all patients. Further, all patients were successfully treated without major complications. The texture, colour and contour of the scalp flap after laser hair removal matched well with the surrounding skin tissues at 2-30-month follow-up. Conclusion: Reconstruction using pre-expanded scalp flaps combined with laser hair removal is an effective and reliable option for facial reconstruction with excellent colour and texture match.